Approach to the level of inclusion of sustainability in university curricula - Azcárate, Pilar; Navarrete, Antonio; García, Esther (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The university plays a role in the integral formation of individuals, which is why we have the obligation to include sustainability in their curricula, so that future practitioners to develop their work from a sustainability that lead them to act in a responsible and committed to its direct environment. The process of sustainability University is not easy and involves a profound transformation of the educational model. The challenge is to find the best way to be effective, way to build each university. Given the current context of European convergence, which advocates a competency-based training, it seems a good time to start the trip. From the UCA, we think that the methodological proposals are a way to include sustainability criteria in the classroom. This research focuses on the methodology used in the classrooms of the University of Cadiz, for teachers interested in the field of sustainability curriculum and examine how these practices are reflected in criteria associated with it.